JUDGMENT VALUE ON CORRUPTION IN ONLINE NEWS: SYSTEMIC FUNCTIONAL LINGUISTICS - Chalimah, Chalimah; Sulistyowati, Heny; Darihastining, Susi; Din, Maaz Ud (FORUM PAEDAGOGIK, 2023)
AbstractExploring the judgment evaluation is conducted to see the pattern of the social sanction and its impact in giving self-reflection to readers as public figures in Indonesia through systemic functional linguistics theory: appraisal. The news text about corruption that are chosen to be analyzed are namely: Lukas Enembe case as a governor, Sudrajat Dimyati case as a judge, and Ferdy Sambo as policeman that involve in criminal case.  The data are analyzed by using appraisal theory in judgment process. The data source is the three online news texts that have mentioned some criticisms to the Indonesian officials, namely: National Tempo News, National Okezone News, and Kompas News. The findings show that each news text has their own way to express the social sanction which uses high negative propriety and negative veracity. The finding is benefit to see how the news text show critical expression that can influence the readers’ emotion. The novelty is finding the pattern of judgment expressions used in three online news texts through appraisal theory but it is limited on the evaluation of judgment.Keywords: judgment, value, corruption cases, appraisal. AbstrakEksplorasi nilai judgment dilaksanakan untuk mengetahui bentuk sanksi sosial dan dampaknya dalam memberikan refleksi diri pada pembaca sebagai tokoh masyarakat di Indonesia melalui teori linguistic sistemik fungsional: appraisal. Teks berita tentang korupsi yang dipilih untuk dianalisa terdiri dari: kasus Lukas Enenbe sebagai seorang gubernur, kasus Sudrajat Dimyati sebagai seorang hakim, dan kasus Ferdy Sambo sebagai seorang polisi yang terlibat kasus kriminal. Data dianalisa dengan menggunakan teori appraisal dalam bentuk proses judgment. Sumber data merupakan tiga teks berita online, yaitu Berita Nasional Tempo, Berita Nasional Okezone, dan Berita Kompas. Temuan menunjukkan bahwa masing-masing teks berita memiliki cara sendiri untuk mengekspresikan sanksi social yang menggunakan negative propriety dan negative veracity yang tinggi. Temuan ini penting untuk melihat bagaimana teks berita menunjukkan ekspresi kritis yang dapat mempengaruhi emosi pembaca. Kebaruan penelitian dalam bentuk pola ekspesi judgment yang digunakan dalam tiga teks berita online melalui teori appraisal namun penelitian ini masih terbatas pada penilaian judgment. Kata Kunci judgment, nilai, kasus korupsi, appraisal.